Exploration of the implementation of project-based learning in technical drawing courses toward - Rizki Fitra; Febri Prasetya; Junil Adri (Journal of Engineering Researcher and Lecturer, 2024)
The instruction of Manufacturing Technical Drawings remains predominantly teacher-centered, lacking diversity in methodologies, thereby causing students to perceive the subject as challenging. This challenge primarily stems from their struggles in comprehending CAD drawing concepts, interpreting existing drawings, and understanding the functionalities of tools in the AutoCAD application, as outlined in the job sheet. Consequently, students' learning achievements fall short of the minimum passing standards SMK Negeri 1 Tanjung Raya set. This research aims to evaluate the impact of project-based learning on learning outcomes in manufacturing technical drawings and assess the quality of instructional tools employed. The study involves two groups, experimental and control groups, selected through cluster random sampling. Data collection includes pretests administered before the instructional intervention and post-tests conducted after both groups receive different treatments. Results reveal that students in the experimental group attain significantly higher average scores than the control group, indicating a substantial influence of project-based learning on learning outcomes. This approach enhances students' understanding, engagement, and critical thinking abilities within the subject area.